Program of Intervention Referred To the Social-Emotional Development of Deaf-Blind Students - Stavrou, Pilios.-D. (Advances in Social Sciences Research Journal, 2016)
The purpose of the study is to develop an interventional educational plan for a deaf-blind student with screened difficulties in socio-emotional development. This is part of a more extensive research in developing the screening inventory for the deaf-blind students’ cognitive and communicative profile. The study uses a qualitative research methodology and adopts an interpretative position. The aim of the inquiry was descriptive. We followed the case study methodology. The application of the interventional program aimed to help the deaf-blind student in discerning and naming the emotions through tactile emotional cards, tactile stories and role playing. The student was offered multisensory and concrete experiences in order to promote socio-emotional development. Through the intervention the student managed to name, recognize and organize her emotions, recognize the feelings of others and started to participate and be engaged in social relationships not only with her educators, but also with other children.